Calf mortality of semi-domesticated reindeer (Rangifer tarandus tarandus) in the Finnish reindeer-herding area - Nieminen, Mauri; Norberg, Harri; Maijala, Veikko (Rangifer, 2013)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> During 1999-2008 calf mortality was studied in six reindeer-herding cooperatives in Northern Finland, where 3942 semi-domesticated reindeer (Rangifer tarandus tarandus) calves were equipped with radio mortality collars. The calves were weighed and earmarked mostly at 2-5 days of age, or at 2-8 weeks of age. Altogether 460 dead radio-collared calves were found from calving in May until winter round-ups in October-January. In northern mountain herding cooperatives, the average mortality of calves varied between 7-12%. On average, 39-54% of calves found dead were attributed to predation. Golden eagles killed 0-3.5% of calves in different years and areas in Ivalo and Käsivarsi cooperatives. Golden eagles were responsible for 33-43% of the cases and 84-93% of all identified predation. Most calves killed by golden eagles were found in July-August and in open areas. Calves killed by golden eagles were significantly (P<0.01) lighter than those not predated. No predation occurred in the Poikajärvi cooperative, but the annual mortality of calves varied between 0-35% in cooperatives near the Russian border. In Oivanki cooperative brown bears killed on average 2% of the radio-collared calves. Most predation (87%) occurred at the end of May and in early June. In the Kallioluoma cooperative, predator-killed calves found comprised 53% and wolf-killed 45%. Predation was 70% of total mortality in the Halla cooperative, and predation by wolf, bear, lynx and wolverine comprised on average 38%, 20%, 9% and 2.3%, respectively. The sex and pelt color did not significantly affect survival of calves. Birth weight of calves killed by bears was significantly (P<0.01) lighter than those not killed, but those calves killed by lynxes were significantly (P<0.05) heavier than that survived. Bears killed calves mainly in May-July, wolves in July-October and lynx in August-December.